2004
DOI: 10.1002/app.20629
|View full text |Cite
|
Sign up to set email alerts
|

Effect of diatomite/polyethylene glycol binary processing aids on the rheology of a metallocene linear low‐density polyethylene

Abstract: Flow performance of metallocene linear lowdensity polyethylene (mLLDPE) containing small amounts of polyethylene glycol (PEG) diatomite and diatomite/PEG binary processing aids respectively was investigated. The mLLDPE melt viscosity is increased by the addition of diatomite, but is decreased by addition of PEG or the diatomite/ PEG binary processing aids. It was also found that the viscosity reduction of mLLDPE with the addition of diatomite/PEG binary processing aid was significantly greater than that obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 22 publications
0
11
0
1
Order By: Relevance
“…In our previous works,14 the effect of the corresponding hybrids of PEG (HD‐a) and PEW (HD‐b) on the rheological properties of mLLDPE was investigated, as shown in Figure 1. HD‐a showed a synergetic effect on the viscosity reduction of mLLDPE.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous works,14 the effect of the corresponding hybrids of PEG (HD‐a) and PEW (HD‐b) on the rheological properties of mLLDPE was investigated, as shown in Figure 1. HD‐a showed a synergetic effect on the viscosity reduction of mLLDPE.…”
Section: Resultsmentioning
confidence: 99%
“…With the addition of more oligomer, the mechanical properties of polymer materials are reduced. In our pervious work, we found that a diatomite/PEG hybrid (HD‐a) shows a synergetic effect on the processability improvement of mLLDPE 14. A small amount of HD‐a reduces the viscosity of mLLDPE dramatically.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies, 20,24,25 we prepared a new type of binary processing aid based on a diatomite/ PEG hybrid. This diatomite/PEG binary processing aid exhibited a synergetic effect on viscosity reduction and sharkskin fracture elimination of mLLDPE, as shown in Figures 7 and 8, respectively.…”
Section: Effect Of Diatomite/peg Binary Processing Aid (Bpa) On the Imentioning
confidence: 99%
“…[15][16][17][18][19] In our previous work, we found that the diatomite/PEG hybrid had a synergetic effect in improving the processability of mLLDPE. 20 A small amount of the diatomite/PEG hybrid dramatically decreased the viscosity of mLLDPE.…”
Section: Introductionmentioning
confidence: 99%
“…[18]. Narrow molecular weight distribution (MWD) and absence of long-chain branching (LCB) result in better mechanical and optical properties [19][20][21][22][23][24]. On the other hand, polymers having such characteristics become more diffi cult to process than conventional ones.…”
Section: Optical Propertiesmentioning
confidence: 99%